GENETIC DIVERSITY ANALYSIS OF MULBERRY SILKWORM (BOMBYX MORI) STRAINS USING RAPD MARKERS - G. A. Bajwa; N. Ahmed; S. H. Shah; M. Adnan (Journal of Animal and Plant Sciences, 2017)
The Mulberry Silkworm Moth (Bombyx mori) is an important commercial insect species having wide genetic diversity. For conservation and breeding programmes, genetic diversity among 18 silkworm strains was analyzed through PCR amplification of the genomic DNA using five Random Amplified Polymorphic DNA (RAPD) primers. The five tested primers generated a total of 368 amplified bands with 48 polymorphic (13.21%). The highest number of polymorphic bands (17.14%) was produced by primer CA-9.The data unraveled a mean genetic similarity distance of 0.546 ranging from 0.110 to 0.991. The mean genetic similarity distance among inbred lines was ranged from 0.124 to 0.943, while the mean genetic similarity distance among hybrids was ranged from 0.129 to 0.984. The highest genetic similarity distance was between C102 and 205PO*J101, while the lowest genetic similarity distance was between 205PO and 205MKD*205PO. The strains were clustered into four groups at 66% similarity level based on UPGMA with complete linkage and squared Euclidean Distance, while they were clustered into two main groups at 33% similarity level. The 206MKD*205PO and J101 were remotely related. Based on these findings it is concluded that the strains have enough genetic diversity which may be conserved in stage of diapause eggs and manipulated for hybrid synthesis breeding programmes.
Keywords: Genetic Diversity; Mulberry Silkworm; PCR; Random Markers; Genetic Relatedness